Matrix Laboratory (Matlab) As an Efficient Pedagogical Tool for Engineering Education, Teaching and Research (Global Journals of Research in Engineering, 2012)
Matrix laboratory can assist the teaching and research of engineering and science education. This paper mirrors how the tedious analytical method of arriving at a solution of mechanical systems and electrical transients can be made less burdensome using MATLAB. The simulated results show that velocity changes with displacement and time. It also highlighted the frictional force or air viscosity inherent in the system as a result of acceleration or retardation and further exhibited the effect of transients on circuit charge and current respectively. The values of this pedagogical tool will enhance a better comprehension of mechanical and electrical systems.
Keywords: MATLAB; Mechanical; System; Transient; Electrical; Analysis